Impact of Proactive Orientation on the Performance of Small and Medium-Scale Enterprises (SMEs) in Delta State, Nigeria - Clinton Emmanuella (CV. Proaksara Global Transeduka, 2025)
This study investigates the impact of proactive orientation on the performance of Small and Medium-Sized Enterprises (SMEs) in Delta State, Nigeria, with a focus on two key dimensions: Goal Setting and Planning (GSP) and Initiative Taking (INT). A sample of 390 SMEs operating in various sectors within Delta State was surveyed to assess how proactive behaviors, such as setting clear goals, planning strategically, and taking initiative, affect business outcomes. The study employs a quantitative research methodology, utilizing structured questionnaires to gather data on proactive orientation and its relationship with SME performance indicators like profitability, growth, and competitive advantage.The findings reveal that both Goal Setting and Planning (GSP) and Initiative Taking (INT) have a significant positive impact on the performance of SMEs. Specifically, businesses that engage in thorough planning and goal setting tend to achieve higher levels of organizational efficiency and profitability. Likewise, SMEs that demonstrate a high degree of initiative-taking are better equipped to seize market opportunities, adapt to challenges, and innovate, leading to improved overall performance.The study recommends that SME owners and managers in Delta State prioritize the development and implementation of structured goal-setting frameworks and proactive planning strategies. Additionally, fostering a culture of initiative-taking within organizations will enhance their ability to respond effectively to changing market conditions and emerging opportunities.In terms of contributions to knowledge, this research highlights the critical role of proactive orientation in driving SME success in a developing economy like Nigeria.